Attempted suicide in a pediatric population, alarming reality (2014)
This article presents the research process that led to the clinical characterization of cases of attempted suicide in the pediatric population treated at the Hospital Infantil Los Angeles in Pasto, between June 2005 and June 2011. 242 records were studied, from a perspective of the general - including clinical and legal - aspects, thus allowing a conceptualization of the term suicide. The description of certain signs and symptoms characteristic of those who have attempted suicide was essential in contributing to identify some possible causes for further understanding this phenomenon, based on the study of 15 variables. The results evidence a progressive increase in the cases of attempted suicide in the pedriatic population, particularly in females, and between 13 and 16 years of age. This situation has developed to a problem that is very difficult to treat; for this reason, it is essential to continue researching, as well as to establish interdisciplinary groups of professionals who can address the problem and create relevant and comprehensive treatments regarding this phenomenon.